Pengaruh Pembinaan Toleransi Antar Umat Beragama Pada Mahasiswa di Kota Gorontalo - Ibnu Rawandhy N. Hula; Fatimah Djafar; Mujahid Damopolii; Ana Mariana; Abdul Rohman (Al-Ulum, 2021)
This study describes tolerance among religious communities and intolerant behavior in students. It also tests the hypothesis of whether there is a significant influence between fostering tolerance among religious communities and heterogeneous student behavior in the formal educational institutions in Gorontalo City. The study used quantitative research with a correlation method through a simple regression. Data were collected using a closed questionnaire, which involved 67 students. This study showed that there is a significant influence between fostering religious tolerance and intolerant behavior of students. This influence is shown by the regression coefficient number of F-count 115.577 with a significance level of 5% (F-table = 3.99). Besides, the value of determination (R Square) = 0,640 illustrates that tolerance among religious communities has a high effect on the tolerance behavior of students. Thus, it can be stated that 64% of the students’ tolerance behavior is affected by the religious communities’ tolerance, and the rest (36%) is influenced by other factors.